Exploring Innovative Approaches: Optimizing Google Classroom for Enhanced Motivation in Science Learning - Pujono, Emmanuel; Maulana, Farid; David, Andrew; Opeyemi, Busari (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to investigate the challenges encountered in utilizing Google Classroom as a learning platform and its implications for motivating students in studying science, with a focus on identifying both internal and external factors affecting students' engagement and interest in the subject. Methodology: This study employs a descriptive qualitative approach to explore the challenges associated with using Google Classroom as a learning tool for motivating science study. Data collection methods include observation, questionnaires, interviews, and documentation. The analysis involves data reduction, presentation (Data Display), and conclusion drawing/verification stages. Data validity is ensured through triangulation of data sources, enhancing the reliability of the findings. Main Findings: The research highlights internal problems like difficulty with Google Classroom, limited smartphone access (1.03%), material comprehension issues, and insufficient teacher explanations. External challenges include lack of family support and teacher interaction. Solutions include providing internet data for infrastructure issues, motivational videos on Google Classroom, video-based learning, and student self-initiated learning via Google, YouTube, and books. Student motivation for science learning through Google Classroom is moderate at 56%. Novelty/Originality of this study: This research contributes novelty by scrutinizing the nexus between Google Classroom and student motivation in science education, addressing a significant gap in current literature. By elucidating nuanced challenges and implications for student engagement, the study offers fresh insights into optimizing digital learning platforms to enhance motivation and learning outcomes in science education amidst the evolving educational landscape shaped by technology.